The interactive Physical and Cognitive Exercise System (iPACES™): effects of a 3-month in-home pilot clinical trial for mild cognitive impairment and caregivers - Anderson-Hanley C (Dove Medical Press, 2018)
Cay Anderson-Hanley,1 Jessica Stark,1 Kathryn M Wall,1 Marisa VanBrakle,1 Makenzie Michel,1 Molly Maloney,1 Nicole Barcelos,1 Kristina Striegnitz,2 Brian D Cohen,3 Arthur F Kramer4 1Healthy Aging & Neuropsychology Lab, Department of Psychology & Neuroscience Program, Union College, Schenectady, NY, USA; 2Computer Science Department & Neuroscience Program, Union College, Schenectady, NY, USA; 3Biology Department, Union College, Schenectady, NY, USA; 4Center for Cognitive & Brain Health, Department of Psychology, Northeastern University, Boston, MA, USA Background: Alzheimer’s and related dementias are on the rise, and older adults and their families are seeking accessible and effective ways to stave off or ameliorate mild cognitive impairment (MCI).Aim: This pilot clinical trial (ClinicalTrials.gov Identifier: 03069391) examined neuropsychological and neurobiological outcomes of interactive physical and mental exercise.Participants and methods: Older adults (MCI and caregivers) were enrolled in a 3-month, in-home trial of a portable neuro-exergame (the interactive Physical and Cognitive Exercise System [iPACES™]), in which they pedaled and steered along a virtual bike path to complete a list of errands (Memory Lane™). Neuropsychological function and salivary biomarkers were measured at pre-, mid-, and posttrial. Ten older adults complied with the recommended use of iPACES (complete dose; ≥2×/wk, 67% of the 15 who also had pre- and postevaluation data). Statistical analyses compared change over time and also change among those with a complete dose vs inadequate dose. Correlations between change in neuropsychological and biomarker measures were also examined.Results: Executive function and verbal memory increased after 3 months (p = 0.01; no significant change was found with an inadequate dose). Change in salivary biomarkers was moderately associated with increasing cognition (cortisol, r = 0.68; IGF-1, r = 0.37).Conclusion: Further research is needed, but these pilot data provide preliminary indications to suggest neuro-exergaming can impact cognitive function, perhaps via neurobiological mechanisms, and as such may provide an effective and practical way to promote healthy aging. Keywords: aging, cognition, MCI, exergame, executive function, neurogame, neuro-exergame